Shakespeare's twenty-first century economics the morality of love and money - Turner, Frederick 1943- (Oxford Univ. Press, 1999)
"In this book, Frederick Turner argues that we need a new, humane, evolutionary economics - a capitalism with a human face - that fully expresses the moral, spiritual, and aesthetic relationships among persons and things. As Turner demonstrates, that new economy was envisaged centuries ago in poetic terms by William Shakespeare." "If we should revise our old, heartless notions of economics, Turner asks, must we find a new language for it? The answer, as Shakespeare shows, is no. Buried within our apparently cold language of finance and business are living meanings. Such words as "bond," "trust," "good," "save," "value," "means," "redeem," "dear," "interest," "honor," "company," "worth," "thrift," "use," "will," "partner," "deed," "fair," "owe," "ought," "treasure," "risk," "royalty," and "venture" contain a pattern of moral obligations and social emotions. Personal bonds and hard-headed business transactions need not occupy separate worlds; we forget at our peril that a nation is also a commonwealth." "Using close readings of the Sonnets, The Winter's Tale, King Lear, The Merchant of Venice, A Midsummer Night's Dream, Henry IV, The Tempest, and Antony and Cleopatra, Turner provides a lexicon of common words and a variety of familial and cultural situations in an economic context."--BOOK JACKET.